Perlindungan Hak Cipta Atas Seni Tari Bali Cendrawasih Berdasarkan Undang -Undang Nomor 28 Tahun 2014 Tentang Hak Cipta - Widyantari Putri, Ida Ayu Puspita; Setiawan, Yudhi (Departement Business Law, Faculty of Law, University of Mataram, 2024)
This research aims to determine the copyright protection for the Balinese Cendrawasih Dance according to Law Number 28 of 2014 concerning Copyright and to determine the legal sanctions if there is a copyright violation of the Cendrawasih Dance according to Law Number 28 of 2014 concerning Copyright. The research method used is normative legal research with a statutory, conceptual, and case approach. This approach uses a descriptive-qualitative data analysis method, namely the normative analysis of legal material obtained from document studies relating to copyright protection for the Balinese Cendrawasih dance according to Law Number 28 of 2014 concerning Copyright. This research explains that legal protection for the Cendrawasih Dance copyright can take the form of preventive protection, namely by registering the copyright with the DJKI. Furthermore, repressive protection can be achieved in two ways; litigation and non-litigation. In the context of copyright infringement in works of art, legal sanctions play an essential role in maintaining justice and respecting the rights of creators. In general, copyright infringement can be divided into two main categories; copyright infringement from a civil perspective and copyright infringement from a criminal perspective. Sanctions for this criminal act are regulated in articles 113, 116, and 118 of Law Number 28 of 2014 because this article states that copyright violators can be subject to imprisonment and fines. Meanwhile, legal sanctions for civil actions are regulated in Article 100 of the Copyright Law because this article gives creators or copyright holders the right to seek compensation for copyright violantions.